DISCUSSION ON THE PAPER: "THE GEOLOGICAL RECORD OF THE OLDEST HISTORICAL TSUNAMIS IN SOUTHWESTERN SPAIN" BY FRANCISCO RUIZ, MANUEL ABAD, JOAQUÍN RODRÍGUEZ VIDAL, LUIS MIGUEL CÁCERES, MARÍA LUZ GONZÁLEZ-REGALADO, MARÍA ISABEL CARRETERO, MANUEL POZO & FRANCISCO GÓMEZ TOSCANO, PUBLISHED IN RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 114(1): 147-156 (2008) - ANTONIO RODRÍGUEZ-RAMÍREZ (Rivista Italiana di Paleontologia e Stratigrafia, 2009)
Comments on the paper “The Geological record of the oldest historical tsunamis in southwestern Spain” by Francisco Ruiz, Manuel Abad, Joaquín Rodríguez Vidal, Luis Miguel Cáceres, María Luz González-Regalado, María Isabel Carretero, Manuel Pozo & Francisco Gómez Toscano.